Protein nutrition and resistance exercise - Evans, W. J. (Canadian Journal of Applied Physiology, 2001)
Strength conditioning will result in an increase in muscle size and this increase in size is largely the result of increased contractile proteins. The mechanisms by which the mechanical events stimulate an increase in RNA synthesis and subsequent protein synthesis are not well understood. Lifting weight requires that a muscle shorten as it produces force (concentric contraction). Lowering the weight forces the muscle to lengthen as it produces force (eccentric contraction). Eccentric contractions produce ultrastructural damage that may stimulate increased muscle protein turnover and a cascade of metabolic events which is similar to an acute phase response and includes complement activation, mobilization of neutrophils, increased circulating and skeletal muscle interleukin-1 and macrophage accumulation. While endurance exercise increases the oxidation of essential amino acids and increases the requirement for dietary protein, resistance exercise results in a decrease in nitrogen excretion, lowering dietary protein needs. Research has indicated that increased dietary protein intake (up to 1.6 g protein kg-1 d-1) may enhance the hypertrophic response to resistance exercise. It has also been demonstrated that in very old men and women the use of a protein-calorie supplement was associated with greater strength and muscle mass gains than did the use of placebo.